Giam ngheo va ru'ng o Viet Nam - Sunderlin, William D.; Huynh Thu Ba (Center for International Forestry Research, 2005)
In Vietnam, as in many developing countries, there is an emerging interest in knowing to what extent and in what ways poverty alleviation can be achieved through use of forest resources, and to what extent poverty alleviation and maintenance or expansion of forest cover are compatible goals. This report seeks to summarize knowledge on this topic that can be obtained from the secondary literature. The methodological challenge is large because there exists a substantial literature on poverty alleviation in Vietnam, and separately a large literature on forestry, but there is little integration between the two. This review of the literature poses questions on: (1) the usefulness of forest resources in past poverty alleviation; (2) the usefulness of forest resources for future poverty alleviation; and (3) the degree of compatibility between poverty alleviation and plans for massive reforestation. The answers we provide to these questions are broad and lack precision, yet they serve as a crucial point of departure for addressing the linked issues of poverty alleviation and improved forest management. The review: (1) proposes additional research to fi ll the information void; (2) encourages the comparative method in this follow-up research; and (3) urges greater collaboration among government agencies responsible for poverty alleviation and forest management. A list of priority research questions is proposed.